2011
DOI: 10.1177/0033688211419379
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Competence in ESL Student Writing

Abstract: In language teaching, emphasis is usually placed on grammatical competence rather than metaphorical competence to improve a learner’s proficiency in the target language. Research has shown that figurative language poses a problem for second language learners whether it is in their ability to interpret, process, or produce metaphors. This affects communication as metaphors are not only restricted to formal texts but are a common feature of everyday language through which individual’s conceptualize and describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…With regard to the type of tests examined to ascertain the influence of nationality, the school covariate also shows that they are verbal reasoning tests but with the rhetorical language domain that is vital for communication skills, like some authors (Kathpalia & Carmel, 2011;Littlemore & Low, 2006) previously noted when assessing the difficulty of L2 learners who have been neglected by teachers and researchers. They are more complex tests and phonological awareness is not evident among the items that showed the importance of nationality as a performance differentiating variable, unlike what was observed for the direct effect of L1 when it showed to be influential.…”
Section: L1 and Nationality: Are They Such Correctmentioning
confidence: 99%
“…With regard to the type of tests examined to ascertain the influence of nationality, the school covariate also shows that they are verbal reasoning tests but with the rhetorical language domain that is vital for communication skills, like some authors (Kathpalia & Carmel, 2011;Littlemore & Low, 2006) previously noted when assessing the difficulty of L2 learners who have been neglected by teachers and researchers. They are more complex tests and phonological awareness is not evident among the items that showed the importance of nationality as a performance differentiating variable, unlike what was observed for the direct effect of L1 when it showed to be influential.…”
Section: L1 and Nationality: Are They Such Correctmentioning
confidence: 99%
“…In addition to previous comments about students producing metaphors that were sometimes unnatural, she notes that instructors should be aware of metaphors used in metalanguage used to provide verbal feedback. Kathpalia and Carmel (2011) found similar results to MacArthur. They looked at a corpus of writing samples from first-year Science & Arts university students in Singapore to analyze types of figurative language problems in the English as a lingua franca context.…”
Section: Metaphor Studies In Other Language Skill Domainssupporting
confidence: 76%
“…She explains that students do not always have an understanding of the motivation for metaphoric words and expressions, their origins or referents, and as a result the ways in which particular words can be used. Kathpalia and Carmel (2011) also investigated the domain of writing, and found that although students tried to incorporate metaphor, it often proved to be unidiomatic or unnatural (not native-like). In Littlemore's 2001 (c) listening comprehension study previously mentioned, she discovered that EAL students had difficulty recognizing figurative language, as well as correctly interpreting the meaning of some English metaphors.…”
Section: English As a Second Language Metaphor Comprehension 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Nacey (2013) manifested the challenges in using novel metaphor, of which non-native speakers faced was mostly the language error. Furthermore, according to Kathpalia and Carmel (2011), cross-cultural competence has an effect on metaphor competence. The misunderstanding in inter-cultural communication causes inaccurate interpretation toward the metaphors in their writing.…”
Section: Teaching Metaphor For Writing Skillmentioning
confidence: 99%